High-resolution transmission electron microscopy with an electrostatic Zach phase plate. (6th May 2016) - Hettler, S; Dries, M; Zeelen, J; Oster, M; Schröder, R R; Gerthsen, D
Abstract: A new method to control lattice-fringe contrast in high-resolution transmission electron microscopy (HRTEM) images by the implementation of a physical phase plate (PP) is proposed. PPs are commonly used in analogy to Zernike PPs in light microscopy to enhance the phase contrast of weak-phase objects with nm-sized features, which often occur in life science applications. Such objects otherwise require strong defocusing, which leads to a degradation of the instrumental resolution and impedes intuitive image interpretation. The successful application of an electrostatic Zach PP in HRTEM is demonstrated by the investigation of single crystalline Si and Ge samples. The influence of the Zach PP on the image formation process is assessed by analyzing the amplitudes of (111) reflections in power spectra which show a cosine-type dependence on the induced phase shift under certain conditions as predicted by theory.